Algal biomass and pigments along a latitudinal gradient in Victoria Land lakes, East Antarctica. Issue 1 (1st January 2016) - Borghini, Francesca; Colacevich, Andrea; Caruso, Tancredi; Bargagli, Roberto
Abstract : It is generally accepted that Antarctic terrestrial diversity decreases as latitude increases, but latitudinal patterns of several organisms are not always as clear as expected. The Victoria Land region is rich in lakes and ponds and spans 8 degrees of latitude that encompasses gradients in factors such as solar radiation, temperature, ice cover and day length. An understanding of the links between latitudinally driven environmental and biodiversity changes is essential to the understanding of the ecology and evolution of Antarctic biota and the formulation of hypotheses about likely future changes in biodiversity. As several studies have demonstrated that photosynthetic pigments are an excellent, although underused, tool for the study of lacustrine algal communities, the aim of the present study was to investigate variations in algal biomass and biodiversity across the latitudinal gradient of Victoria Land using sedimentary pigments. We test the hypothesis that the biodiversity of freshwater environments decreases as latitude increases. On the basis of our results, we propose using the number of sedimentary pigments as a proxy for algal diversity and the sum of chlorophyll a and bacteriochlorophyll a with their degradation derivatives as an index of biomass. Overall, our data show that biomass and diversity decrease as latitude increases but local environmental conditions, in particular, natural levels of eutrophy, can affect both productivity and diversity.